PREVALENCE OF MISCONCEPTIONS AND PRESENTATION OF COVID-19 POST-VACCINATION SYMPTOMS AMONG HEALTH CARE WORKERS OF KARACHI, PAKISTAN - Iqra Shahid Hussain; Tooba Noor; Quratulain Amir; Washdev, Washdev; Farina Hanif (Journal of Pakistan Psychiatric Society, 2022)
Objectives To determine reasons towards reluctant behavior of health care workers against COVID-19 vaccination and symptoms experienced by vaccinated individuals. Study Design Cross sectional study design. Place and duration of study Dow University of Health Sciences (OJHA Campus), Civil Hospital and Sindh Institute of Urology and Transplant from March 2021 till May 2021. Subjects & methods Altogether 260 samples were recruited and analyzed to investigate the pattern of unwillingness for vaccination, diversity in presentation of symptoms and approaches for its subsidence after administration of COVID-19 vaccine. Data was analyzed via IBM SPSS Statistics version 25.0 and results were expressed in frequencies and percentages Results Altogether 41.7% of vaccinated participants developed post vaccination symptoms including fever, flu, body ache, headache and allergic reactions. In spite of experiencing post vaccination symptoms a large group of people (65.5%) had not taken any medications to improve their indications. Conclusion Hesitation regarding immunization with COVID-19 vaccination was reported in study population. Social media played a key role in spreading misconceptions regarding vaccination.